Isomorfismo Institucional: pressões sociais que moldam as ações das associações comerciais e empresariais - Benkendorf, Eda Cristina (2021)
The Commercial and Business Associations (ACES), or Trade Bussines Associations, are organizations through which member companies seek to promote and legitimize their common interests, strengthening and developing the economic environment in which they are located. They are subject to the pressures of the environment in which they are inserted, aiming to reduce uncertainties and acting in accordance with the most socially acceptable way, in order to legitimize their actions, even if it is not the most efficient way. This way of acting tends to produce effects that make them more homogeneous. This dissertation aimed to understand how the social pressures existing in the organizational field of the ACES, contribute to shape the actions of these entities. It had four specific objectives: (i) map the organizational field of the ACES; (ii) identify the presence and types of isomorphic forces in the organizational field of the ACES; (iii) verify how the isomorphic forces exert pressure for the homogenization of the organizational environment of the ACES and; (iv) explain which factors influence the Associativism Index. Guided by the Institutional Theory, in the New Institutional Sociology aspect, eight ACES that are part of the Coordination of Commercial and Business Associations of the Western Paraná State - CACIOPAR - were analyzed. The study used, as sources of information, data and evidence, from interviews carried out with fifteen of its representatives. This is a descriptive work, with a qualitative approach and a survey and documentary research typology, using content analysis and the Atlas TI. The results indicate that the social pressures existing in the organizational field of the ACES, shape the actions of these entities, making them homogeneous in terms of organizational structure and values, due to the philosophy of associativism. The coercive isomorphism, exercised by the legislation in force and by the entity's own bylaws, the mimetic isomorphism, through the modeling of the structure, actions, and processes of the ACES that are taken as models, and the normative isomorphism, related to the standardization of the ACES, were identified. It was found that two factors are present in the three mechanisms, namely the bylaws and accountability. A significant disparity was observed between the associative indexes of the researched entities. The results indicate that the size of the entity, the amount of services offered and the commitment of the board of directors and collaborators to gain new members influence the formation of the index. The organizational field of the ACES is strongly marked by values linked to associativism. The constant search for improvements for the promotion and integration among the different economic activities of the region, made by means of cooperation among the players, tends to lead to the homogenization of the ACES' actions, within the same organizational field. For future research, it is suggested that the role of specific actors of this organizational field be evaluated, based on a methodology that considers the perspective between actors and relationship networks. It is advisable that researchers seek to understand the specific role of accounting mechanisms, in the management and accountability process of the ACES, which may contribute to shape the actions of these entities. It is also suggested that future research should analyze the ratio of services offered and the associativism index, under a quantitative methodological perspective.